PERAWATAN LUKA PERENIUM PADA ASUHAN KEBIDANAN IBU NIFAS DENGAN MENGGUNAKAN REBUSAN DAUN BINAHONG - Beril Triana; Silvia Mona; susanti (Universitas Batam, 2023)
Perineal rupture is a cause of postpartum maternal bleeding. Postpartum hemorrhage is the main cause of 40% of maternal deaths in Indonesia. Improper perineal wound care can result in infection. Non-pharmacological therapy that can be given to speed up wound healing so that infection does not occur is to use binahong leaves. Provide comprehensive midwifery care for postpartum mothers. The midwifery care that is applied is the treatment of perineal wounds using a decoction of binahong leaves. The type of research used in the preparation of practice reports is descriptive research using the case study method. Midwifery care related to Basic Midwifery Skills by treating perineal wounds using binahong leaves for postpartum mothers to accelerate wound healing has been carried out. This is in accordance with the theory that the boiled water of binahong leaves can accelerate the healing of perineal wounds.